First Photographic Evidence of Short-eared Owl Asio flammeus (Pontoppidan, 1763) from Sarlahi district, Nepal - Rokka, Prashant; Bajagain, Santosh; Pradhan, Aavas (FORESTRY: Journal of Institute of Forestry, Nepal, 2021)
This paper presents the first photographic record of the Short-eared Owl Asio flammeus, one of the least studied species of Nepal during opportunistic survey. The new record for Bagmati River stretch on 26 November 2020 were five pairs of Asio flammeus in a grassland dominated area adjacent to agricultural land in Sarlahi district. With this record, conservation efforts in the area should include the regular monitoring and controlled human activities. Moreover, it is crucial to develop conservation awareness on the importance of owls in the ecosystem. It is also necessary to change the perception and attitude of people towards owl which are perceived as sign of evil.